Sapere Aude — Dare to Be Wise: Elbert D. Glover - Elbert D. Glover (Health Behavior Research, 2024)
Sapere Aude – Dare to Be Wise is a unique editorial conversational interview-type feature. It is an attempt to deep dive into an Academy members’ background, formative experience, and education – specifically, to extract factors that contributed to their development and evolution as a professional, as well as their success as a prominent researcher in the health behavior arena. Every Academy member selected has a different story to tell and numerous models for success will emerge from this exploration of the membership. That said, the first of what we hope to be a series of enlightening interviews is Elbert D. Glover, the founder of The Academy.